Pengaruh Disiplin Kerja dan Motivasi Kerja Terhadap Kinerja Karyawan Pada PT. Pertama Logistics Service - Irma Sari Octaviani; Lidya Pricilla (JIMF (Jurnal Ilmiah Manajemen Forkamma), 2020)
The research objective is to determine the effect of work discipline and work motivation on employee performance at PT Pertama Logistics Service partially and simultaneously. Research method with associative method. 50 respondents are the sample. Multiple linear regression is a data analysis technique. The results of this study are as follows: The more disciplined an employee is in working, the more employee performance increases. The effect of these variables is significant positive or (0.000 <0.01). The more an employee is motivated to be enthusiastic about work, the more employee performance increases. The effect of these variables is significant positive or (0.000 <0.01). The more disciplined an employee is in working and the more motivated an employee is to be enthusiastic at work when combined simultaneously, the more employee performance increases. The effect of these variables is significant positive or (0.000 <0.01).